Sustaining Organizational Outcomes in Manufacturing Firms: The Role of HRM and Occupational Health and Safety - Ali Ateeq; Abd Al-Aziz Al-refaei; Mohammed Alzoraiki; Marwan Milhem; Ali Nasser Al-Tahitah; Abdulhadi Ibrahim (MDPI, 2024)
Indexed by Scopus